Closing the gap : the quest to understand prime numbers - Neale, Vicky (Oxford University Press, 2017)
Mathematicians have recently made dramatic progress on the Twin Primes Conjecture, which asserts that there are infinitely many pairs of prime numbers that differ by 2. This book will describe two stories: that of the recent work on the Twin Primes Conjecture, and in parallel the related ideas from the previous two thousand years of mathematics.